(untitled) (Revista INTEREDU11, 2022)
This article is part of a research conducted over a group of Chilean secondary-education chemistry teachers who participated in continuing education workshops. The objective of this study was to characterize the evolution of epistemological conceptions about the Nature of Sciences, and the importance of the metadisciplinary foundation for the improvement of teaching practices. This qualitative research of a collective case study has been framed over descriptive approach and revealed that knowledge on epistemological conceptions linked to the Nature of Sciences, within the framework of a learning community, and also allowed to highlight the importance of promoting teacher reflection and a change in its pedagogical discourse.